PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KOMITMEN ORGANISASI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI SULAWESI TENGGARA - Sri Hasriani; Rahmat Madjid; Sudirman Zaid; Juharsah Juharsah; Hartini Hartini; Eliyanti Agus Mokodompit (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This research was conducted with the aim of knowing the influence of leadership and work environment on organizational commitment and employee performance at the Education and Culture Office of Southeast Sulawesi Province. The research method used is descriptive quantitative analysis method, and uses SEM analysis methods. The data used in this study are primary and secondary data. The population in this study amounted to 110 people with the sampling technique using the census. Data were processed statistically using AMOS program tools. The results of this study indicate that (1) Leadership has a positive and significant effect on employee organizational commitment, (2) The work environment has a positive but insignificant effect on employee organizational commitment, (3) Leadership has a negative and insignificant effect on employee performance, (4) Environment work has a positive and significant effect on employee performance, (5) Organizational commitment has a positive and significant effect on employee performance at the Education and Culture Office of Southeast Sulawesi Province. The higher the employee's organizational commitment, the higher the performance shown by the employees.